2001
DOI: 10.1053/jhep.2001.21050
|View full text |Cite
|
Sign up to set email alerts
|

Signal Pathway Involved in the Development of Hypoxic Preconditioning in Rat Hepatocytes

Abstract: Ischemic preconditioning improves liver resistance to hypoxia and reduces reperfusion injury following transplantation. However, the intracellular signals that mediate the development of liver hypoxic preconditioning are largely unknown. We have investigated the signal pathway leading to preconditioning in freshly isolated rat hepatocytes. Hepatocytes were preconditioned by 10-minute incubation under hypoxic conditions followed by 10 minutes of reoxygenation and subsequently exposed to 90 minutes of hypoxia. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 44 publications
7
102
1
2
Order By: Relevance
“…Collagenase (type I), HEPES, chelerythrine, phenylmethylsulfonyl fluoride, propidium iodide, leupeptin, aprotinin, curcumin, 8-bromo-cGMP, ANP, NP receptor (NPR)-C agonist des-(Gln 18 , Ser 19 ,Gly 20 ,Leu 21 ,Gly 22 )-ANP fragment 4-23 amide (C-ANP), and SB203580 were purchased from Sigma Chemical Co. (St. Louis, MO). KT5823 was from ICN Biomedicals (Costa Mesa, CA), and PD98059 was from Calbiochem-Novabiochem (San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Collagenase (type I), HEPES, chelerythrine, phenylmethylsulfonyl fluoride, propidium iodide, leupeptin, aprotinin, curcumin, 8-bromo-cGMP, ANP, NP receptor (NPR)-C agonist des-(Gln 18 , Ser 19 ,Gly 20 ,Leu 21 ,Gly 22 )-ANP fragment 4-23 amide (C-ANP), and SB203580 were purchased from Sigma Chemical Co. (St. Louis, MO). KT5823 was from ICN Biomedicals (Costa Mesa, CA), and PD98059 was from Calbiochem-Novabiochem (San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Studies performed on isolated and perfused liver have shown that resistance to hypoxia induced by preconditioning is associated with the release of nitric oxide and adenosine (Peralta et al, 1997;Peralta et al, 1999), downregulation of caspase 3 activity (Yadav et al, 1999) and decreased production of TNFα by Kupffer cells (Peralta et al, 2001). We have shown that the preconditioning-induced cytoprotection can be reproduced in isolated rat hepatocytes by a short cycle of hypoxiareoxygenation or by direct stimulation of the adenosine A2A-receptor with the agonist CGS21680 (Carini et al, 2001a). The signaling pathway was shown to involve a trimeric G-inhibitor protein, the phospholipase C, PKC isoenzymes and the p38-MAPK (Carini et al, 2000;Carini et al, 2001a).…”
Section: Introductionmentioning
confidence: 94%
“…Mechanistic studies have revealed that adenosine, bradykinin, or perhaps other circulating factors signal through G-protein coupled receptors [26] . This initiates a signaling cascade involving activation of protein kinase C [27] , heat shock factor 1 [28] , and mitogen-activated protein kinase [29] . Activation of these receptors during preconditioning result in up regulation of multiple systems capable of attenuating IRI including superoxide dismutase, heat shock proteins, and eNOS [30][31][32] .…”
Section: Ischemic Preconditioningmentioning
confidence: 99%